Response of YPM x Ross 708 male broilers to diets containing varying inclusions of phytase, calcium butyrate, and bacitracin methylene disalicylate during the grower and finisher periods–part 2: Intestinal health and physiology - Joseph P. Gulizia; Zubair Khalid; Maria T. Terra-Long; Jose I. Vargas; Jose R. Hernandez; Wilmer J. Pacheco; James T. Krehling; Kenneth S. Macklin; William A. Dozier, III; Klint W. McCafferty; Ruediger Hauck (Poultry Science)
This study evaluated the effects of calcium butyrate (CB) and bacitracin methylene disalicylate 50 (BMD) combined with different phytase concentrations on broiler intestinal health and physiology. Day-old YPM x Ross 708 male broilers (2,880) were distributed in 72 floor pens and assigned to 1 of 9 treatments (8 replicates/treatment). This experiment was a factorial arrangement including 2 phytase concentrations (500 or 1,500 FTU/kg) and 4 microbiota modulating feed additive levels (MMFA; (1) none, (2) only CB (0.5 g/kg of diet), (3) only BMD (55 mg/kg of diet), or (4) both CB and BMD). Additionally, a negative control without phytase and MMFA was included. Intestinal permeability was assessed on d 27. Jejunum wall and cecal content samples were collected on d 28 and 42 to assess jejunum villus height (VH), crypt depth, tight-junction and mucin gene expression, cecal microbiome diversity, and predicted bacterial metabolic pathways. Phytase and MMFA did not influence intestinal permeability (P > 0.05). Combining both CB and BMD with 1,500 FTU/kg of phytase compared to 500 FTU/kg lowered d 28 VH (P ≤ 0.05). Jejunal expression of CL-1, CL-4, CL-5, and ZO-2 on d 28 as well as CL-2 on d 42 changed between MMFA when combined with 1,500 FTU/kg of phytase but not 500 FTU/kg (P ≤ 0.05). Day 42 Pielou's evenness increased when 1,500 FTU/kg of phytase was combined with both CB and BMD compared to no MMFA (P ≤ 0.05). The cecal microbial beta diversity was not influenced by phytase, MMFA, or their interaction (P > 0.05). Overall, broiler intestinal health and physiology were influenced by CB and BMD depending on phytase concentration, demonstrating the complex interactions between these feed additives.